2015
DOI: 10.1016/j.crhy.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties of transition metal pnictides and chalcogenides: Angle-resolved photoemission spectroscopy and dynamical mean-field theory

Abstract: Electronic Coulomb correlations lead to characteristic signatures in the spectroscopy of transition metal pnictides and chalcogenides: quasi-particle renormalizations, lifetime effects or incoherent badly metallic behavior above relatively low coherence temperatures are measures of many-body effects due to local Hubbard and Hund's couplings. We review and compare the results of angle-resolved photoemission spectroscopy experiments (ARPES) and of combined density functional dynamical mean field theory (DFT+DMFT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 171 publications
(303 reference statements)
2
40
0
Order By: Relevance
“…The small renormalization factor (1.1) indicates that the electronic correlations in SrNi 2 As 2 are much weaker than that in the Fe-based superconductors, in which the overall bandwidth is typically renormalized by a factor of 2 ∼ 5 [8,9]. In addition, we do not observe in SrNi 2 As 2 any indication of orbital-selectivity, which contrasts with the Fe-pnictide superconductors, for which the bands with d xy character are renormalized twice as much as the other bands [13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small renormalization factor (1.1) indicates that the electronic correlations in SrNi 2 As 2 are much weaker than that in the Fe-based superconductors, in which the overall bandwidth is typically renormalized by a factor of 2 ∼ 5 [8,9]. In addition, we do not observe in SrNi 2 As 2 any indication of orbital-selectivity, which contrasts with the Fe-pnictide superconductors, for which the bands with d xy character are renormalized twice as much as the other bands [13].…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the Fe-based family of superconductors, the parent compounds of the Ni-based superconductors do not show any magnetic ordering. While electronic correlations are responsible for a renormalization of the band structure of the Fe-based superconductors by a typical factor of 2∼5 [8,9], recent angleresolved photoemission spectroscopy study (ARPES) reported that the band dispersions are renormalized by a factor of 1∼2 in BaNi 2 P 2 [10] and by a factor of 1.4 in TlNi 2 Se 2 [11], suggesting weaker electronic correlations in the Ni-based superconductors. Since Hund's coupling is believed to play a significant role to tune the correlation strength in these materials, a systematic study and comparison is of importance.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic correlations are widely believed to play a major role for unconventional superconductivity in the Fe-based superconductors [1]. It was established theoretically that the strength of the electronic correlations in these materials is tuned by the filling of the 3d shell in presence of a large Hund's coupling [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This could explain why the valence band near E F is only renormalized by a factor of  1.35 (Fig. 2e), which is much smaller than the renormalization factor in Fe-pnictide parent or holedoped superconducting Fe-pnictide compounds (typically  2 -4) [11,[25][26][27] whose Fe 3d orbitals are partially filled. In Fig.…”
mentioning
confidence: 99%